EFFECT OF SLOW DEEP BREATHING AND AROMATHERA-PY OF LAVENDER (LAVANDULA ANGUSTIFOLIA) ON BLOOD PRESSURE IN HYPERTENSION PATIENTS IN PANTI WERDHA ILOMATA OF GORONTALO CITY - Yusrin Aswad (LP2M Universitas Bina Mandiri Gorontalo, 2019)
Increased blood pressure that lasts for a long time (persistent) can cause damage to the kidneys (kidney failure), heart (coronary disease) and brain (causing stroke) if not detected early. Do deep breathing and slow, will provide an opportunity for the body to perform and direct diaphragmatic breathing can change lives to activate the physiology centers in the brain relaxation. Whereas Steam and smoke This essential oil can also affect a person's psychological state through stimuli received by the nerve endings of the olfaction found in the lining of the nasal lenders, or the area of ​​nerve response in other organs through which the essential oil vapor drops. The purpose of this study: determine the effect of slow deep breathing and lavender aromatherapy on blood pressure in patients with hypertension. Quasi experiment with the design